2021
DOI: 10.1186/s12974-021-02081-7
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally misfolded proteins exacerbate ischemic stroke-induced neuroinflammation and brain injury

Abstract: Background Protein aggregates can be found in peripheral organs, such as the heart, kidney, and pancreas, but little is known about the impact of peripherally misfolded proteins on neuroinflammation and brain functional recovery following ischemic stroke. Methods Here, we studied the ischemia/reperfusion (I/R) induced brain injury in mice with cardiomyocyte-restricted overexpression of a missense (R120G) mutant small heat shock protein, αB-crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…2 ). These findings further highlight a significant role of the heart on brain functional recovery following stroke [ 47 ].…”
Section: Multimorbid Conditions That Influence Stroke Outcomesmentioning
confidence: 86%
See 1 more Smart Citation
“…2 ). These findings further highlight a significant role of the heart on brain functional recovery following stroke [ 47 ].…”
Section: Multimorbid Conditions That Influence Stroke Outcomesmentioning
confidence: 86%
“…A recent study from our group highlights the important effect of aberrant protein aggregation in the cardiac muscle on ischemic stroke-caused brain injury and functional recovery in mice. Specifically, mice with cardiomyocyte-restricted transgenic expression of a missense (R120G) mutant alpha B-crystallin (CryAB R120G ) exhibit significantly increased glial activation, infarct volume, impaired functional recovery, learning and memory deficits, and increased neuroinflammation following surgically induced cerebral ischemia/reperfusion [ 47 ].…”
Section: Multimorbid Conditions That Influence Stroke Outcomesmentioning
confidence: 99%
“…Only in the A2780 WT cell line, we were able to observe their small amount (HSPB5 and HSPB6). A few animal models have shown that secretion of small HSPs via exosomal cargo in pathophysiological events such as ischemic stroke or myocardial infarction has huge implications on their recovery (Liu et al, 2021[ 35 ]; Yu et al, 2019[ 64 ]). However, there is limited data about their involvement in malignant progression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mitochondrial dysfunction is mostly associated with the pathogenesis of neurological conditions [ 94 , 95 , 96 , 97 , 98 ]. The causes for the neurological diseases also include deleterious mitochondrial DNA [ 99 ], accumulated misfolded proteins [ 100 ], problems in the calcium influx [ 101 ], flaws in the mitochondrial oxidative phosphorylation systems (OXPHOS) [ 102 ], elevated levels of ROS [ 103 ], and apoptosis of neuron cells [ 104 ]. After the cellular death, released DNA, proteins and cellular debris promote microglia, initiate inflammation and damage the tissue [ 95 ].…”
Section: Allicin As a Neuroprotective Agent To Fight Against Neurological Diseasesmentioning
confidence: 99%